Isokinetic evaluation of professional soccer players following anterior cruciate ligament reconstruction (ACLR) - Parpa, K.; Paludo, C. A.; Michaelides, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The management of ACL ruptures involves surgical intervention and the implementation of comprehensive rehabilitation programs. Nevertheless, athletes reintegrating into regular activities post-ACLR confront a greater risk of recurrent ACL injury, especially if they fail to satisfy established return-to-play criteria. These criteria include assessments of knee stability, isokinetic strength, the duration since ACL surgery, hop performance, and self-reported questionnaires. This study aimed to evaluate isokinetic peak torque, hamstring to quadriceps torque rations and bilateral strength (torque) differences in professional soccer players who underwent ACLR compared to healthy soccer players as a control group. METHODS: A total of 150 professional soccer players (75 ACLR and 75 aged-matched controls, age 26.25±4.96 and 25.12±5.00 yrs., height 177.77±21.69 and 179.76±5.58cm, body weight 76.89±8.71 and 77.95±6.43 kg, respectively) participated in the study. The time after surgery was 185.31±9.44 days, with 44 players undergoing the procedure on the left leg and 31 players on the right leg. RESULTS: Statistical analysis indicated significant differences (p<0.01) in the quadriceps torque of the ACLR leg compared to the control group (203.51±35.81 vs 244.85±26.02 m/s) along with the ACL leg and the non-ACL leg of the experimental group (203.51±35.81 vs 249.29±35.64 m/s) at an angular velocity of 60 degrees/sec. Similarly, significant differences were demonstrated in the hamstring torque between the ACLR leg and control (171.07±27.30 vs 183.88±25.30 m/s) as well as the hamstring to quadriceps ratio of the ACLR leg and control (85.12±11.52 vs 75.48±10.28) at an angular velocity of 60 degrees/sec. No significant differences were identified in the quadriceps torque of the non-ACL leg and control. Also, significant bilateral differences (p<0.01) were indicated in the quadriceps torque production between the experimental and control groups (Q-Q difference 18.64±5.94 vs 5.45±3.54 for the experimental and control groups, respectively). The aforementioned significant differences persisted even when the players were tested at an angular velocity of 300 degrees/sec. CONCLUSION: Our results demonstrated noteworthy differences among the soccer players (ACLR-leg vs control) in all isokinetic strength parameters, except for the non-ACL leg (quadriceps). Based on our results, clinicians and rehabilitation experts should take into account the isokinetic parameters when assessing the players` readiness for a return to sports following ACLR.